2018
DOI: 10.1155/2018/5428157
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Injection of Mitomycin C for the Treatment of Pharyngoesophageal Stenosis Refractory to Endoscopic Treatment with Dilatation in Patients Treated for Head and Neck Cancer

Abstract: Background Management of pharyngoesophageal stenosis (PES) in patients after head and neck cancer (HNC) treatment remains a challenge. It is not uncommon that PES is refractory to dilation sessions. This study aimed at evaluating the efficacy of Mitomycin C (MMC) endoscopic injection for the treatment of refractory pharyngoesophageal stenosis. Patients and methods This is a prospective study in patients with dysphagia following head and neck cancer treatment, without evidence suggestive of tumor recurrence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Gusmon-Oliveira et al [15] concluded that the repeated injection in the short interval of MMC in refractory pharyngoesophageal stenosis in patients after head and neck cancer is not recommended, this finding was in great difference with our results, this can be easily explained by different age group and different nature of both diseases.…”
Section: Discussioncontrasting
confidence: 97%
“…Gusmon-Oliveira et al [15] concluded that the repeated injection in the short interval of MMC in refractory pharyngoesophageal stenosis in patients after head and neck cancer is not recommended, this finding was in great difference with our results, this can be easily explained by different age group and different nature of both diseases.…”
Section: Discussioncontrasting
confidence: 97%
“…Other studies that did not meet inclusion criteria for this systematic review have reported complications such as fungal infection, keloid scarring, granuloma and mediastinal emphysema following MMC in airway surgery. An oesophageal trial was interrupted because all of the first three patients experienced intense neck pain after MMC injection 43 . It is, of course, difficult to attribute causality of these outcomes to MMC.…”
Section: Discussionmentioning
confidence: 99%
“…These authors used cotton sponges soaked in MMC or spraying as a method of application. None of these authors applied MMC by direct infiltration at the stricture site despite it being reported as safe and more effective in adult series because of more precise dose calculation and exact stricture site application (15)(16)(17)(18). Most articles, including controlled trials, have proven MMC to be beneficial and safe (2,4,5).…”
Section: Discussionmentioning
confidence: 99%